(untitled) (UNED Research Journal, 2024)
Introduction: For the production of fruit crops, it is important to know the relationship between climatic variables and crop phenology. There are few studies on this topic in pitahaya cultivation in Costa Rica. Objective: to evaluate the type of relationship between climate and the emission of sprouts in the cultivation of pitahaya cv. San Ignacio. Methods: We carried out the research between 2017 and 2019. We evaluated the following variables: number of vegetative sprouts (NVS), number of reproductive sprouts (NRS), average temperature (Ta), minimum temperature (Tmin), maximum temperature (Tmax), relative humidity (RH), and rainfall (R). We calculated Spearman correlations between variables. Results: We did not find statistically significant correlations between NVS and the other analyzed variables. On the other hand, we observed a significant positive correlation between the NRS and minimum temperature (r=0.52**), rainfall (r=0.36*), and relative humidity (r=0.33*). These results indicate that as precipitation, relative humidity, and minimum temperature increase, the number of reproductive sprouts also increases. We additionally identified correlations between NVS, NRS, and climatic variables during the months prior to sprouting. Conclusion: No defined pattern was observed in the emission of vegetative sprouts, while the emission of reproductive sprouts occurred mainly during the initial and middle phases of the rainy season. Furthermore, it was observed that generally, during the emission of reproductive sprouts, few or no vegetative sprouts were produced.